2007
DOI: 10.1016/j.physletb.2007.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear modification factor for charged pions and protons at forward rapidity in central Au+Au collisions at 200 GeV

Abstract: We present spectra of charged pions and protons in 0-10% central Au+Au collisions at √ s N N = 200 GeV at mid-rapidity (y = 0) and forward pseudorapidity (η = 2.2) measured with the BRAHMS experiment at RHIC. The spectra are compared to spectra from p+p collisions at the same energy scaled by the number of binary collisions. The resulting nuclear modification factors for central Au+Au collisions at both y = 0 and η = 2.2 exhibit suppression for charged pions but not for (anti-)protons at intermediate p T . The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 54 publications
(25 reference statements)
1
7
0
Order By: Relevance
“…Interestingly the suppression is stronger at forward rapidities where one would expect parton energy loss to be less. This is consistent with the pattern seen for π − mesons in Au+Au collisions [38].…”
Section: A Particle Spectrasupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly the suppression is stronger at forward rapidities where one would expect parton energy loss to be less. This is consistent with the pattern seen for π − mesons in Au+Au collisions [38].…”
Section: A Particle Spectrasupporting
confidence: 91%
“…PHENIX has suggested that a similar effect may explain why at high p T R AA is almost the same at √ s N N = 63 and 200 GeV [42]. It is also possible that at forward rapidity initial state effects such as nuclear shadowing are reducing particle production, [37,38].…”
Section: A Particle Spectramentioning
confidence: 95%
“…Recently, the nuclear modification factor (NMF) has been extensively investigated for different particles at various collision energies in relativistic heavy-ion collisions (HIC) [1][2][3][4]. These studies indicate that the NMF, which can be represented either by the modification factor between nucleus-nucleus (AA) collisions and protonproton (pp) collision R AA or the one between the central collisions and peripheral collisions R CP , is very useful for the study of the quantitative properties of the nuclear medium response when the high speed jet transverses it.…”
Section: Introductionmentioning
confidence: 99%
“…To study nuclear medium effect in Au+Au collisions, it is convenient to introduce a ratio R cp of the particle yield in central collisions to that in peripheral collisions [16,40]. Both yields are normalized by corresponding nucleon-nucleon binary collision numbers N coll (binary scaling),…”
Section: Nuclear Modification Factor Rcp Of Protons and Pionsmentioning
confidence: 99%
“…The nuclear modification factor (NMF) has been extensively studied in relativistic heavy ion collisions in recent years [16][17][18][19][20][21]. In these studies, unanimous results have demonstrated that the NMF is suppressed at high p T owing to partonic energy loss effect.…”
Section: Introductionmentioning
confidence: 99%